(untitled) (Huellas, 2017)
This article deals with businessmen as social actors in the rural space of the pampas, and analyses a specific type: those occupying the in-between positions in the rural structure. Such a differentiation was made taking into account, not just the size of their rural business but also other dimensions related to production profiles, work organization strategies and social aspects like territorial links and the structure of work relations. Our work is based on a case study carried out in three departments of the province of Buenos Aires, and on a sample including different types of actors among which we differentiate those businessmen who share a similar profile constructed in an atmosphere of tension between different logics present in the rural space of the pampas.